Familial Restless Legs Syndrome: A Family with all Female Patients - Akpinar, Cetin Kursad; Turker, Hande; Aygun, Dursun; Aytac, Emrah (Acad Medical Sciences I R Iran, 2017)
Background: Restless legs syndrome (RLS) is a chronic condition characterized by odd sensations in the body, most commonly in the legs and an irresistible urge to move them. More than half of the patients with RLS have a family history. Most of the RLS cases are women and most of the families show characteristics of an autosomal dominant pedigree. Here, we shall present a family consisting only of women; to our knowledge, such a family has not been reported yet. Methods: The family presented here met the diagnosis criteria specified by International Restless Legs Syndrome Study Group (IRLSS). Clinical characteristic are described along with demographic properties. Results: The patients were between 12 and 59 years of age with a mean age of 35.3 +/- 14.4 years. All 7 cases were women. The pedigree of the patients exhibited an autosomal dominant inheritance pattern. Conclusions: The present family tree indicates that familial RLS can exhibit a heredity pattern which shows autosomal dominant inheritance. The present family is still under follow-up. Future research is required to support the present data.
Keywords: Autosomal dominant inheritance; familial; pedigree; restless legs syndrome